Hubungan Tingkat Stres dengan Keteraturan Siklus Menstruasi pada Mahasiswi S1 Kebidanan Universitas Muhammadiyah Semarang - Sherkia Ichtiarsi Prakasiwi; Sutiara Sinta (Yayasan Literasi Sains Indonesia, 2025)
Background: Menstrual cycle regularity is an important indicator of women's reproductive health. Factors such as stress, lifestyle, and academic activities can affect menstrual cycle regularity, especially in female students who face high demands during their studies. Objective: This study aims to analyze menstrual cycle regularity and the factors that influence it in undergraduate Midwifery students at Muhammadiyah University of Semarang. Method: Descriptive quantitative research with a cross-sectional approach was conducted on 77 female students. Data were collected using a questionnaire and analyzed univariately to describe the frequency distribution of menstrual cycle regularity. Results: Based on the research that has been done, it was found that 49 female students, or 63.6% of respondents, had regular menstrual cycles, while 28 female students, or 36.4%, experienced menstrual irregularities. Students who experienced regular menstrual cycles and experienced low stress were 31 respondents, while those who were irregular were 4 respondents, then students who experienced low stress and regular cycles were 16 respondents followed by those who were irregular as many as 11 respondents, for students who experienced severe stress and experienced regular menstrual cycles as many as 2 people, the remaining 13 people experienced irregular menstrual cycles. Conclusion: There is a significant relationship between stress levels and menstrual cycle regularity, this is proven by the sig value (p-value <0.05) which is 0.000.